2016
DOI: 10.1007/s11738-016-2191-x
|View full text |Cite
|
Sign up to set email alerts
|

Differential growth and yield responses of salt-tolerant and susceptible rice cultivars to individual (Na+ and Cl−) and additive stress effects of NaCl

Abstract: Negative impacts exerted by sodium (Na ? ) and chloride (Cl -) ions individually as well their possible additive effects (under NaCl) were evaluated on growth and yield reductions in rice, besides investigating whether salt-tolerant genotypes respond differentially than their sensitive counterparts. Though both Na ? and Cl -ions get accumulated in plant tissues under NaCl stress, most research has historically been aimed to decipher harmful effects induced by Na ? ions. Accordingly, physiological and molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 41 publications
6
40
2
Order By: Relevance
“…Earlier, Arshi et al (2010) also observed a significant reduction in Na/K in salt-stressed Glycine max as a result of Ca supplementation and it has been suggested that calcium and potassium show much similarity in behavior during the selective transport of ions across the membranes (Boursier and Läuchli 1990). Decreases in yield attributes by NaCl stress in the present study corroborates with the findings of Kumar and Khare (2016) in rice. Size of grain and its shape is very important as it determines its quality.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Earlier, Arshi et al (2010) also observed a significant reduction in Na/K in salt-stressed Glycine max as a result of Ca supplementation and it has been suggested that calcium and potassium show much similarity in behavior during the selective transport of ions across the membranes (Boursier and Läuchli 1990). Decreases in yield attributes by NaCl stress in the present study corroborates with the findings of Kumar and Khare (2016) in rice. Size of grain and its shape is very important as it determines its quality.…”
Section: Discussionsupporting
confidence: 91%
“…Salinity stress decreases the yield and yield components in rice seedlings (Mohammadi et al 2013). Kumar and Khare (2016) also reported reduced grain yield and quality of yield in rice seedlings under NaCl stress. Accumulation of Na + has been reported to hamper many important biological functions such as photosynthesis, respiration, and uptake of nutrients (Ahmad et al 2015, Ahmad et al 2016b, Ahanger and Agarwal 2017.…”
Section: Introductionmentioning
confidence: 92%
“…High proline contents represent Ni stress in plants growing in contaminated media [44]. The susceptible cultivars show less proline contents as compared to resistant ones when subjected to the same level of abiotic stress [45]. The increased proline contents improve plant resistance against heavy metal stress [46].…”
Section: Resultsmentioning
confidence: 99%
“…The resistance and response of plants to a salt stress varies according to its species or varieties or genotypes or variety and environment which could be attributed to the biological dissimilarities between the species or varieties or genotypes, plant growth, and composition and concentration of the salt stress conditions (Bertazzini et al, 2018; Filichkin et al, 2018; Shabala et al, 2013). Many reports have shown that short term salinity stress significantly affects the germination rate, seedling and root growth as well as ion composition, levels of relative water content, photosynthetic pigments, proline content, level of membrane lipid peroxidation as well as the amounts of reducing sugars and total protein (Dugasa et al, 2019; Sarabi et al, 2017; Kumar and Khare, 2016). These physiological and biochemical indices multivariate cluster analysis been used for classification of salt-sensitive and salt-tolerant varieties so that they can further be used in plant breeding programmes.…”
Section: Introductionmentioning
confidence: 99%
“…The crop is well adapted to heat, drought and poor soil stress in marginal and degraded soils. Further, its cereals have comparatively better antioxidant and nutraceutical properties and superb storage qualities which lack in other cereals (Kumar et al, 2016). All these attributes make finger millet one of the important and promising plant genetics resources for agriculture, and food and nutritional security and alleviation of poverty of poor farmers who live in arid, infertile and marginal lands.…”
Section: Introductionmentioning
confidence: 99%